Effects of Support Matrix for Xylanase Immobilisation on Alginate Hydrogel Beads - Siti Sabrina, Mohd Sukri; Mimi Sakinah, A. M. (Penerbit Universiti Malaysia Pahang, 2017)
Enzymes serving as biocatalysts and play an important roles in many industrial field. However, the limitation of enzyme usage due to its high cost and unstable conditions of Enzymes serving as biocatalysts and play an important roles in many industrial field. However, the limitation of enzyme usage due to its high cost and unstable conditions of soluble enzyme to harsh conditions lead to findings an alternative to enhance the enzyme efficiency by immobilisation (insoluble enzyme). The present work reported a combination of immobilisation technique of xylanase by entrapment and covalent binding on alginate hydrogel beads. Xylanase enzyme was effectively immobilised within the support matrix, alginate hydrogel beads by entrapment and covalent binding on the surface of beads using glutaraldehyde as a cross-linked agent. The effects of support matrix comprised of sodium alginate concentration (% w/v) and calcium chloride, CaCl2 (M) were studied in order to obtain a better immobilisation yield. The suitable concentration of sodium alginate and CaCl2 to ensure a robust and stable hydrogel beads with higher immobilisation yield were formed as a support matrix for xylanase immobilisation. The analysis of xylanase activity was determined using dinitrosalicyclic (DNS) acid reagent method. Maximal enzyme immobilisation yield (>80 %) was achieved at 3.0 % w/v of sodium alginate concentration and 0.3 M of CaCl2. The study shows the support matrix of hydrogel beads gave a significant impact towards the immobilisation yield of xylanase.